2006
DOI: 10.1210/me.2005-0170
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Growth Hormone Receptor Signaling

Abstract: GH has been of significant scientific interest for decades because of its capacity to dramatically change physiological growth parameters. Furthermore, GH interacts with a range of other hormonal pathways and is an established pharmacological agent for which novel therapeutical applications can be foreseen. It is easy to see the requirement for a number of postreceptor mechanisms to regulate and control target tissue sensitivity to this versatile hormone. In recent years, some of the components that take part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
139
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 130 publications
2
139
2
2
Order By: Relevance
“…Regulation of the GH intracellular signalization pathway occurs through a complex mechanism involving the coordinated action of various negative regulators, whose main targets apparently are JAKs and STATs phosphorylated by activated GHR [33]. The studies by Studzinski et al with two mechanisms indicated that the GH intracellular signalling control observed in HO GH-transgenic zebrafish utilizes SOCS-1 and SOCS-3 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the GH intracellular signalization pathway occurs through a complex mechanism involving the coordinated action of various negative regulators, whose main targets apparently are JAKs and STATs phosphorylated by activated GHR [33]. The studies by Studzinski et al with two mechanisms indicated that the GH intracellular signalling control observed in HO GH-transgenic zebrafish utilizes SOCS-1 and SOCS-3 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous leptin improves glucose homeostasis in ob/ob and lipodystrophic mice [44,45]. It also improves glucose homeostasis in humans with congenital leptin deficiency or lipodystrophy, but has little effect on classic obesity [46][47][48]. In addition to its role in energy homeostasis, leptin has important endocrine functions, including the regulation of the hypothalamic-pituitary-adrenal and gonadal axes, bone development, immune response, angiogenesis, and hematopoiesis, which will not be reviewed here [49,50].…”
Section: Adipokines Directly Involved In Energy Homeostasismentioning
confidence: 99%
“…GH induces the expression of several negative regulators of GH signaling: SOCS1, 2, and 3, CIS [70,71] .…”
Section: Growth Hormone (Gh) Jak-stat Signalingmentioning
confidence: 99%